2010
DOI: 10.1177/0022034510375826
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Metalloceramic and Zirconia-based Ceramic Crowns

Abstract: Despite the increasing utilization of all-ceramic crown systems, their mechanical performance relative to that of metal ceramic restorations (MCR) has yet to be determined. This investigation tested the hypothesis that MCR present higher reliability over two Y-TZP all-ceramic crown systems under mouth-motion fatigue conditions. A CAD-based tooth preparation with the average dimensions of a mandibular first molar was used as a master die to fabricate all restorations. One 0.5-mm Pd-Ag and two Y-TZP system cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
1
30

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 25 publications
7
66
1
30
Order By: Relevance
“…The fatigue of tested groups was not considered in this study. Certainly fatigue aspect is often the clinical phenomena particularly in aged restorations [26][27][28][29]. Further studies should investigate the aging of all-ceramic systems and compare the data with the findings of this study.…”
Section: Discussionmentioning
confidence: 53%
“…The fatigue of tested groups was not considered in this study. Certainly fatigue aspect is often the clinical phenomena particularly in aged restorations [26][27][28][29]. Further studies should investigate the aging of all-ceramic systems and compare the data with the findings of this study.…”
Section: Discussionmentioning
confidence: 53%
“…The use of accelerated life tests in dental research has been reported in a series of studies concerning the reliability of a variety of prosthetic restorative systems where a remarkable resemblance between the resulting failure modes was observed when compared to clinical failures [22][23][24][25]. Similar findings were reported when accelerated life tests were used in implant-borne reconstructions [19].…”
Section: Introductionmentioning
confidence: 72%
“…Various ceramic materials have been developed, and in some studies, their mechanical and physical characteristics have been evaluated and reported on [5][6][7] . While all-ceramic crowns are aesthetically superior, there have been concerns about their clinical application due to their relatively lower mechanical strength than metal-ceramic crowns 8) .…”
Section: Introductionmentioning
confidence: 99%